Factors associated with road traffic injuries and their severity : a prospective cohort study - Kovačević, Jelena, liječnica (Array, 2020)
Road traffic injuries cause considerable losses to individuals, their families, and to nations as a whole. Factors related to road traffic injuries and to the severity of such injuries have not been fully elucidated or evaluated. The aim of this study was to explore factors related to road traffic injuries and their severity in cohort of 200 road traffic accident (RTA) survivors from Eastern Croatia. Sustaining injury was associated with rural residence (p=0.032), lower education level (p=0.001), unemployment (p=0.001), being single (p=0.014), under average self-assessed economic status (p=0.001), alcohol abstinence (p=0.018), use of medications (p=0.031), self-assessed life-threat (p<0.001), pain after the RTA (p<0.001), hospitalization after the RTA (p<0.001), hospitalization duration (p<0.001), surgery (p=0.048), rehabilitation following the RTA (p=0.001) and PTSD symptoms (p=0.001). Injury severity was associated with lower education level (p=0.013), unemployment (p=0.004), being single (p=0.017), under average self-assessed economic status (p<0.001), alcohol abstinence (p=0.042), use of medications (p=0.014), self-assessed life-threat (p<0.001), pain after the RTA (p<0.001), being a pedestrian or a cyclist (p=0.011), hospitalization after the RTA (p<0.001), hospitalization duration (p<0.001), surgery (p<0.001), rehabilitation following the RTA (p=0.001), depression (p<0.001) and PTSD symptoms (p<0.001). In order to more adequately prevent road traffic injuries knowledge about factors associated with such injuries and their severity should be base for the creation of specific prevention programs at regional and national level.